PEDAGOGICAL POSSIBILITIES OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE FORMATION OF ETHNIC AND CULTURAL AWARENESS AMONG YOUNGER CHILDREN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
For modern social and cultural environment of educational institutions are characterized by multi-ethnicity, as well as the ambiguous attitude of one social group to the members of different cultural and ethnic communities.Therefore, one of the important task is to bring up children in the spirit of peace and respect for all nationalities and peoples; the formation of children communication skills ability to interact with representatives of various peoples and faiths.The achievement of this goal is possible through focused multicultural education, the targets of which are defined in strategy of the state in ensuring ethnic harmony and harmonization of interethnic relations.In the article the authors focus on the formation of ethnic and cultural awareness among younger children: reveal the essence and structure of ethnic awareness, present the results of diagnostics of level of formation at children of primary school, consider the possibility of using information and communication technologies in the classroom and in extracurricular activities.The article reveals the pedagogical potential of using Internet resources in the creation ofpresentations, movies, virtual tours, virtual museums, thematic projects and Web-based quests, virtual newspapers.The article discusses the features of the organization of individual and group work of children, collaboration with teachers and parents.